Magnetic coupling of vortices in a two-dimensional lattice. (29th October 2015) - Nissen, D; Mitin, D; Klein, O; Arekapudi, S S P K; Thomas, S; Im, M-Y; Fischer, P; Albrecht, M
Abstract: We investigated the magnetization reversal of magnetic vortex structures in a two-dimensional lattice. The structures were formed by permalloy (Py) film deposition onto large arrays of self-assembled spherical SiO2 -particles with a diameter of 330 nm. We present the dependence of the nucleation and annihilation field of the vortex structures as a function of the Py layer thickness (aspect ratio) and temperature. By increasing the Py thickness up to 90 nm or alternatively by lowering the temperature the vortex structure becomes more stable as expected. However, the increase of the Py thickness results in the onset of strong exchange coupling between neighboring Py caps due to the emergence of Py bridges connecting them. In particular, we studied the influence of magnetic coupling locally by in-field scanning magneto-resistive microscopy and full-field magnetic soft x-ray microscopy, revealing a domain-like nucleation process of vortex states, which arises via domain wall propagation due to exchange coupling of the closely packed structures. By analyzing the rotation sense of the reversed areas, large connected domains are present with the same circulation sense. Furthermore, the lateral core displacements when an in-plane field is applied were investigated, revealing spatially enlarged vortex cores and a broader distribution with increasing Py layer thickness. In addition, the presence of some mixed states, vortices and c-states, is indicated for the array with the thickest Py layer.